تأثير نموذج النمو الوجهي على الصفات الشكلية للعظم السنخي في منطقة القواطع السفلية (دراسة شعاعية باستخدام التصوير المقطعي المخروطي المحوسب CBCT) (Latakia University Journal -Medical Sciences Series, 2019)
Objective: The purpose of this study was to investigate association between facial growth pattern and the morphology of the lower incisor’s alveolar bone using cone beam computed tomography (CBCT). Materials and methods: From a sample of 168 CBCT scans, 83 scans were selected to be included in the study. CBCT-synthesized lateral cephalograms were used to categorize subjects into three groups based on their facial growth pattern. Using Ondemand 3D software, measurements of alveolar height, thickness and width of each lower incisor were carried out. ANOVA test was done for statistical analyses. Results: Compared to the other two groups, group with vertical facial pattern had larger buccal and lingual alveolar height, thinner buccal and lingual alveolar thickness and smaller buccolingual alveolar width with significant difference (P<0.005(. Furthermore, group with horizontal facial pattern presented thicker buccal and lingual alveolar thickness, larger buccolingual alveolar width and smaller buccal and lingual alveolar height with significant difference (P<0.005( Conclusions: There is a statistically significant effect of facial growth pattern on the morphology of the lower incisors’ alveolar bone. Subjects with vertical facial pattern can be at increased risk of moving incisors beyond alveolar bone support when subjected to marked anterio-posterior incisor movement. الهدف: هدف الدراسة تقييم العلاقة بين نموذج النمو الوجهي والصفات الشكلية للعظم السنخي في منطقة القواطع السفلية وذلك باستخدام التصوير المقطعي المخروطي المحوسب. المواد والطرق: تم انتقاء 83 صورة من أصل 165 من الصور المقطعية المخروطية المحوسبة CBCT لإدخالها في الدراسة. استخدمت الصور السيفالومترية الجانبية المستخلصة من صور CBCT من أجل تقسييم أفراد العينة إلى ثلاث مجموعات وذلك بناءاً على نموذج النمو الوجهي الخاص بهم. أجريت القياسات الخاصة بارتفاع وثخانة وعرض العظم السنخي عند كل قاطعة من القواطع السفلية باستخدام برنامج Ondemand 3D. كما استخدم اختبار ANOVA أحادي الجانب من أجل التحليل الإحصائي. النتائج: أظهرت عينة النموذج الوجهي العمودي ارتفاع سنخي لساني ودهليزي أكبر مع ثخانة سنخية لسانية ودهليزية وعرض سنخي دهليزي لساني أصغر بشكل دال إحصائياً (P<0.05) مقارنة مع المجموعتين الأخرتين. علاوة على ذلك، أظهرت مجموعة النموذج الوجهي الأفقي ثخانة سنخية لسانية ودهليزية وعرض سنخي دهليزي لساني أكبر مع ارتفاع سنخي دهليزي ولساني أصغر بشكل دال إحصائياً أيضاً (P<0.05). الاستنتاجات والتوصيات: يؤثر نموذج النمو الوجهي على الصفات الشكلية للعظم السنخي في منطقة القواطع السفلية بشكل دال إحصائياً. نوصي بأخذ الحذر عند تحريك القواطع السفلية بالاتجاه الأمامي الخلفي للأفراد ذوي النموذج الوجهي العمودي من تحريكها خارج العظم القاعدي السنخي الأمامي.